1995
DOI: 10.1073/pnas.92.23.10599
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation-dependent I kappa B alpha phosphorylation marks the NF-kappa B inhibitor for degradation via the ubiquitin-proteasome pathway.

Abstract: The nuclear translocation of NF-KcB follows the degradation of its inhibitor, IKBcx, an event coupled with stimulation-dependent inhibitor phosphorylation. Prevention of the stimulation-dependent phosphorylation of IKcBa, either by treating cells with various reagents or by mutagenesis of certain putative IKcBai phosphorylation sites, abolishes the inducible degradation of IKcBX. Yet, the mechanism coupling the stimulation-induced phosphorylation with the degradation has not been resolved. Recent reports sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
284
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(291 citation statements)
references
References 45 publications
6
284
0
1
Order By: Relevance
“…The arrow indicates the position of the speci®c NF-kB complex commonly a prerequisite for its ubiquitination and degradation (May and Ghosh, 1998). We used the protease inhibitor ALLN (N-Acetyl-Leucyl-LeucylNorleucinal) and phosphatase inhibitors (see Materials and methods) in an attempt to detect a phosphorylation-induced shift of IkBa (Alkalay et al, 1995) after treatment with CPT. Cells were treated with ALLN as indicated (Figure 6b), then with TNF-a or CPT, and the cytoplasmic proteins were extracted in the presence of phosphatase inhibitors for analysis by Western blotting.…”
Section: Ikba Degradation In Normal and At ®Broblastsmentioning
confidence: 99%
“…The arrow indicates the position of the speci®c NF-kB complex commonly a prerequisite for its ubiquitination and degradation (May and Ghosh, 1998). We used the protease inhibitor ALLN (N-Acetyl-Leucyl-LeucylNorleucinal) and phosphatase inhibitors (see Materials and methods) in an attempt to detect a phosphorylation-induced shift of IkBa (Alkalay et al, 1995) after treatment with CPT. Cells were treated with ALLN as indicated (Figure 6b), then with TNF-a or CPT, and the cytoplasmic proteins were extracted in the presence of phosphatase inhibitors for analysis by Western blotting.…”
Section: Ikba Degradation In Normal and At ®Broblastsmentioning
confidence: 99%
“…Given the fact that several transcription factors, such as HIF1a and NF-kB, are under the control of the UPP (Alkalay et al, 1995;Cho et al, 2001), we hypothesized that impairment of the UPP in RPE could result in altered gene expression that promotes the development of AMD-like phenotypes. To test this hypothesis, we inhibited proteasome activity in cultured RPE and assessed the effects on the expression and secretion of growth factors and chemokines that may be involved in the development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…The proteasome, a large multi-subunit protease complex, has been shown to be involved in these processes [32][33][34] and it has been suggested that additional proteases, such as calpains, may play a further role [35]. In addition to these mechanisms, the existence of proteolysisindependent pathways for NF-B activation has been postulated, although their involvement in cytokine gene expression is not known [36,37].…”
Section: Introductionmentioning
confidence: 99%